The Development Of Educational Tourism Takoma Honey Breeding In Nagori Sait Buttu Saribu Pematang Sidamanik District Simalungun - Prinsi Rigitta (Jurnal Scientia, 2024)
The background to this research is the active role of stakeholders in the development of the TAKOMA Honey Bee Breeding Educational Tourism. The aim of this research is to find out the role of stakeholders in the development of TAKOMA Honey Bee Breeding educational tourism. This research was conducted using qualitative methods. There are two types of data sources for this research, namely primary data and secondary data, with data collection techniques in the form of participant observation, in-depth interviews and document reviews. The role of stakeholders in developing the TAKOMA Honey Bee Breeding Educational Tourism can be seen in 5 forms of assistance, namely; provision of infrastructure to increase honey production, infrastructure for tourism development, tourism development guidance and training, mentoring and guidance, promotion.